Enhancing Credit Risk Management In Microfinance: A Study On Addressing Non-Performing Loans At Rukun Ikhtiar Savings And Loan Cooperative - Indri Sanabila Saffana; Raden Aswin Rahadi (Utan Kayu Publishing, 2025)
The existence of financial cooperatives is crucial for supporting economic activities, particularly for small and medium-sized enterprises (SMEs). However, the increasing rate of Non-Performing Loans (NPLs) poses a significant risk to their sustainability. This study investigates the Rukun Ikhtiar Savings and Loan Cooperative (KSP RI), which is confronted with a persistent rise in non-performing loans (NPLs). Utilizing a dual approach, encompassing both quantitative and qualitative methods, this study assesses the financial performance and the efficacy of credit risk management at KSP RI. The quantitative analysis found that NPL, Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), and Operating Expenses to Operating Income (BOPO) significantly affect Return on Asset (ROA), which highlights KSP RI's financial performance against increasing NPLs. Qualitative analysis using the Five C's credit framework, identified weaknesses in lending procedures, leading to the extension of credit to unqualified borrowers. To address this issue, the study recommends, implementing stricter lending policies with Five Cs framework, enhancing staff capacity through training and utilizing technology to improve risk monitoring. These findings provide insights for KSP RI and other microfinance institutions in strengthening credit risk management and provide a framework for future research.